Rare bird documentation form for Greater Scaup at Lakin Slough, 1985 - Myers, Robert K.et al (1985)
Rare bird documentation form for two Greater Scaups at Lakin Slough in Guthrie County, IA on April 16, 1985. Epson - sheet feed